Single vs Multi-drain Probabilistic Analyses of Soil Consolidation via Prefabricated Vertical Drains - Bari, Md. Wasiul; Shahin, Mohamed; Soubra, A. (cIRcle, the Digital Repository of the University of British Columbia, 2015)
Natural soils are one of the most inherently variable in the ground. Although the significance of inherent soil variability in relation to reliable prediction of consolidation rates of soil deposits has long been realized, there have been few studies that addressed the issue of soil variability for the problem of ground improvement by prefabricated vertical drains (PVDs). Despite showing valuable insights into the impact of soil spatial variability on soil consolidation by PVDs, available stochastic works on this subject are based on a single drain (or unit cell) analysis. In a spatially variable soil, however, the condition of unit cell may be violated. Therefore, in a probabilistic context, it is necessary to assess the feasibility of performing an analysis based on the unit cell concept as compared to the multi-drain analysis. In this study, a rigorous stochastic finite element modeling approach that allows the nature of soil spatial variability to be considered in a quantifiable manner, both for the single and multi-drain cases, is presented. It is shown that with proper input statistics representative of a particular domain of interest, both single and multi-drain analyses yield almost identical results. This study also highlights the importance of proper modeling of soil spatial variability in design of ground improvement by PVDs.